IMPLEMENTATION OF BANDUNG CITY REGIONAL REGULATIONS CONCERNING PUBLIC ORDER, PEACE AND COMMUNITY PROTECTION: Study: Motorcycle Gang Violence in 2021-2023 - Gusman Maulana Sidiq; Rahman Mulyawan; Neneng Yani Yuningsih (DIA: Jurnal Administrasi Publik, 2025)
The fundamental problem in the research is that even with the presence of Bandung City Regional Regulation Number 9 of 2019 concerning Public Order, Peace and Community Protection, basically the majority of the community does not feel safe because of the disturbing actions carried out by motorbike gangs. This research uses a qualitative approach with a descriptive approach. The data collection techniques in this research are observation and literature study, while the data analysis techniques are through data reduction, presentation and drawing conclusions. The results of research in the field show that the implementation of Bandung City Regional Regulation Number 9 of 2019 concerning Public Order, Peace and Community Protection has not run optimally. This is because the crime rate, one of which is committed by motorbike gangs in the city of Bandung, is still increasing to this day. Data from the Bandung City Central Statistics Agency shows that of the 1,707 crimes that occurred during 2023, at least around 775 cases were caused by other criminal cases, one of which included street violence involving motorbike gangs. Furthermore, based on data that researchers obtained regarding the number of violence committed by motorbike gangs in the city of Bandung in the last three years, the highest number occurred in 2023 with 54 cases.